Nutraceutical and functional food processing technology - Boye, Joyce I (Wiley Blackwell, 2015)
Current and Emerging Trends in the Formulation and Manufacture; Functional and Sustainable Food â€“ Biophysical Implications of a â€œHealthyâ€ Food System; Key Considerations in the Selection of Ingredients and Processing; Quality Evaluation and Safety of Commercially Available; Novel Health Ingredients and Their Applications in Salad;...